2018
DOI: 10.1007/s40519-018-0577-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of appetite awareness training among African-American women who binge eat

Abstract: Level V, qualitative descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 46 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…For example, several studies have reported that, compared with White women, Black women may experience less subjective distress and shame related to engagement in BE behaviors (Franko, Becker, Thomas, & Herzog, ; Napolitano & Himes, ). This racial difference might be due to the presence of cultural norms that may permit eating larger portions of food and/or using food for emotional coping (Beauboeuf‐Lafontant, ; Goode et al, ). The experience of marked distress is a key diagnostic criterion for BED (American Psychiatric Association, , ); if Black women indicate binge‐eating behavior, yet also indicate the absence of marked distress, which may be influenced by cultural factors and norms, their eating pathology might be mischaracterized or underestimated.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, several studies have reported that, compared with White women, Black women may experience less subjective distress and shame related to engagement in BE behaviors (Franko, Becker, Thomas, & Herzog, ; Napolitano & Himes, ). This racial difference might be due to the presence of cultural norms that may permit eating larger portions of food and/or using food for emotional coping (Beauboeuf‐Lafontant, ; Goode et al, ). The experience of marked distress is a key diagnostic criterion for BED (American Psychiatric Association, , ); if Black women indicate binge‐eating behavior, yet also indicate the absence of marked distress, which may be influenced by cultural factors and norms, their eating pathology might be mischaracterized or underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…Though the reasons for these disparities are likely complex, further investigation of the factors associated with retention in treatment for BE/BED in this population might be helpful. In a recent feasibility trial that included Black women with BE behaviors, retention was nearly 90%; the authors report that scheduling intervention sessions in a familiar community location and in the evening might have contributed to study retention (Goode et al, ). Additionally, in focus groups following the feasibility trial, participants acknowledged the benefit of feeling support from the facilitator and other group members (Goode et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations